AB0783 The relationship between the degree of skin involvement and joint activity in patients with psa: experience from the corrona registry. (15th June 2017) - Mease, PJ; Etzel, CJ; Lisse, JR; Armstrong, AW; Huster, WJ; Rebello, S; Dodge, R; Muram, T; Al, S Sawah-Folian; Murage, MJ; Greenberg, JD; Malatestinic, W
Abstract : Background: Prior studies have shown inconsistent relationships between skin and joint symptoms in patients with comorbid psoriasis (PsO) and psoriatic arthritis (PsA) 1–3 . Objectives: To characterize the relationship between skin severity and joint activity in patients with comorbid PsA and PsO at enrollment. Methods: Data from the U.S. Corrona PsA/spondyloarthritis (PsA/SpA) registry were obtained from the period 3/21/2013– 9/30/2016. Inclusion criteria included a diagnosis of PsA, a history of PsO, and age greater than 18 years. PsA patients were evaluated for skin severity as defined by Body Surface Area (BSA) and joint activity as defined by the level of clinical disease activity index (CDAI). Patient characteristics, including current and prior PsA medication use, were obtained during the enrollment visit. We evaluated the relationship of skin severity (BSA) and joint activity (CDAI) with multi-variable linear regression. Results: 1, 542 patients met inclusion criteria: 52.9% were women with mean (SD) age 53.7 (13.2) years, with median 9.0 years PsA disease duration, and 71 (4.6%) with fibromyalgia. 266 (18%) patients were on no DMARD therapy, 430 (29%) were on csDMARDs only, 616 (42%) were on first line biologic/targeted synthetic (ts)DMARD therapy, and 172 (12%) were on second line biologic/tsDMARD therapy. The relationship between skin severity and joint activity was statistically significant (p<0.0001) with a correlation of 0.183. Results were similar when adjusting separately for treatment and for duration of PsA and PsO. Greater age, female gender, higher dactylitis count, not achievement of MDA, higher HAQ, and patient reported pain and fatigue affected the relationship. Conclusions: The relationship between skin severity and joint activity is statistically significant and varies by age, gender, MDA, HAQ, and patient reported pain and fatigue. This suggests degree of skin involvement is important to take into account when evaluating PsA patients. References: Gottlieb AB, Mease PJ, Mark Jackson J, Eisen D, Amy Xia H, Asare C, Stevens SR: Clinical characteristics of psoriatic arthritis and psoriasis in dermatologists' offices. J Dermatolog Treat 2006;17:279–287. Jones SM, Armas JB, Cohen MG, Lovell CR, Evison G, McHugh NJ: Psoriatic arthritis: outcome of disease subsets and relationship of joint disease to nail and skin disease. Br J Rheumatol 1994;33:834–839. Cohen MR, Reda DJ, Clegg DO: Baseline relationships between psoriasis and psoriatic arthritis: analysis of 221 patients with active psoriatic arthritis. Department of Veterans Affairs Cooperative Study Group on Seronegative Spondyloarthropathies. J Rheumatol 1999;26:1752–1756. Acknowledgements: Corrona, LLC has been supported through contracted subscriptions in the last two years by AbbVie, Amgen, AstraZeneca, BMS, Crescendo, Eli Lilly and Company, Genentech, GSK, Horizon Pharma USA, Janssen, Momenta Pharmaceuticals, Novartis, Pfizer, Roche and UCB. Disclosure of Interest: P. Mease Grant/research support from: Celgene, Novartis, Abbvie, Amgen, BMS, Janssen, Lilly, Pfizer, Sun, UCB, Consultant for: AbbVie, Amgen, BMS, Crescendo, Celgene, Corrona, Demira, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, Sun, Zynerba, Speakers bureau: Abbvie, Amgen, BMS, Celgene, Crescendo, Genentech, Janssen, Novartis, Pfizer, UCB, C. Etzel Consultant for: Merk, Employee of: Corrona, LLC, J. Lisse Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, A. Armstrong Grant/research support from: AbbVie, Janssen, Lilly; speaker's bureau: AbbVie, Lilly, Consultant for: AbbVie, Amgen, Janssen, Merck, Lilly, Celgene, Novartis, and Pfizer, W. Huster Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, S. Rebello Employee of: Corrona, LLC, R. Dodge Employee of: Corrona, LLC, T. Muram Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, S. Al Sawah-Folian Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, M. Murage Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, J. Greenberg Shareholder of: Corrona, LLC, Consultant for: Genentech, Janssen, Novartis and Pfizer, Eli Lilly, Employee of: Corrona, LLC, W. Malatestinic Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company